SNIFFING AND CANNABIS CONSUMPTION DURING PRE-ADOLESC MULTIVARIATE ANALYSIS OF PREDISPOSING FACTORS - Pinazo Hernandis, Sacramento; Pons Diez, Javier; Carreras Rouma, Anabel (Anales de Psicología / Annals of Psychology, 2002)
This paper presents the results of a research aime exploration of the relationship between the consumption of stitutionalized drugs among pre-teens, and a series of hypot related variables (such as self-concept, family communicate the consumption of other drugs), and sociostructural variablas age, environment, siblings, scholarly performance) as w research relies on a survey of 564 primary education student both sexes, aged between 11 and 15. Multyvariate analysis w ried out in order to find out the relationship between the cotion of sniffable drugs and cannabis, and the above mentionables. At a second stage, those variables that showed significferences were again analized in order to find out which o provided an stronger predictability of drug consumption variables proved to be the consumption of institutionalizeand self-concept.